VD_FINDINFO Décision / 2018 / 731 vom 12. September 2018 - VD Tribunal cantonal (2018)
LIBÉRATION CONDITIONNELLE, PRONOSTIC, REJET DE LA DEMANDE, INDEMNITÉEN GÉNÉRAL | 6 par. 1 CEDH, 86 al. 1 CP, 113 CPP (CH)